2018
DOI: 10.1007/s10661-018-6467-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and health risk assessment of natural fluoride of drinking groundwater resources of Isfahan, Iran, using GIS

Abstract: Fluoride (F) contamination in groundwater can be problematic to human health. This study evaluated the concentration of fluoride in groundwater resources of Isfahan Province, the central plateau of Iran, and its related health issues to the inhabitant populations. For this purpose, 573 drinking groundwater samples were analyzed in 2016 by using the spectrophotometric method. Non-carcinogenic health risks due to F exposure through consumption of drinking water were assessed using the US EPA method. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 44 publications
0
10
0
3
Order By: Relevance
“…According to the research report in India [27], the mean concentration of fluoride in ground drinking water was lower than Ethiopian rift valley mean value. Similarly, other studies on fluoride content in ground drinking water in Iran [28, 29], revealed lower mean concentration than the fluoride concentration in Ethiopian rift valley ground water. The difference might be the effect of the east African rift valley which is known with active volcanic eruption resulting fluoride release and availability of different water sources for drinking in another part of the world.…”
Section: Discussionmentioning
confidence: 56%
“…According to the research report in India [27], the mean concentration of fluoride in ground drinking water was lower than Ethiopian rift valley mean value. Similarly, other studies on fluoride content in ground drinking water in Iran [28, 29], revealed lower mean concentration than the fluoride concentration in Ethiopian rift valley ground water. The difference might be the effect of the east African rift valley which is known with active volcanic eruption resulting fluoride release and availability of different water sources for drinking in another part of the world.…”
Section: Discussionmentioning
confidence: 56%
“…to study the occurrence of groundwater F levels and related health issues. 16,17 The present study aims to provide a more accurate view of the groundwater issue in Sri Lanka. The study aims to identify both hazardous and safe groundwater sources, and suggest feasible and economically viable solutions that can be implemented at the community level to mitigate dental fluorosis in Sri Lanka.…”
Section: Geographic Information System (Gis) Has Been Used Previouslymentioning
confidence: 99%
“…Geographic information system (GIS) has been used previously to study the occurrence of groundwater F levels and related health issues . The present study aims to provide a more accurate view of the groundwater issue in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
“…Fluoride contamination in groundwater has been recognized as a widespread international problem, which influences millions of people in many regions [35][36][37][38]. Drinking groundwater with a high concentration of fluoride may endanger human health and cause fluorosis or other diseases.…”
Section: Introductionmentioning
confidence: 99%